A regioselective step-by-step C60Cl6 functionalization approach affords a novel family of C60Ar5Th′Th′′H fullerene derivatives with promising antiviral properties. Issue 26 (14th March 2023) - Bolshakova, Valeriya S.; Kraevaya, Olga A.; Peregudov, Alexander S.; Markov, Vitaliy Yu.; Kostyuk, Svetlana V.; Schols, Dominique; Shestakov, Alexander F.; Troshin, Pavel A.
Abstract : A novel reaction of fullerene derivatives C1-C60Ar5Th′ with substituted thiophenes Th′′H leads to the unknown family of compounds C1-C60Ar5Th′Th′′H with antiviral, antioxidant properties and three different types of functional addends. Abstract : We report a novel reaction of the recently discovered family of fullerene derivatives C 1 -C60 Ar5 Th′ with thiophene derivatives Th′′H yielding a previously unknown family of C 1 -C60 Ar5 Th′Th′′H compounds with three different types of functional aromatic addends attached to the carbon cage. The discovered reaction paves a way to the synthesis of novel C60 fullerene derivatives with promising antioxidant and antiviral properties.